Detection of nontuberculous mycobacteria in raw, post-treated and tap water in Metro Manila - Rullan, June Kathyleen H.
Nontuberculous mycobacteria (NTM) are commonly found in the environment. They are known as opportunistic pathogens causing pulmonary infection, lymphadenitis, skin and soft tissue disease, skeletal infection, disseminated disease, and catheter-related infection (Wagner et al, 2004; Dailloux et al, 1999; US EPA, 1999). In the Philippines, the prevalence of mycobacteria other than tuberculosis (MOTT; also known as NTM) is 31.9 per thousand population nationwide (Rivera et al., 2001). However, there were no published studies on the existence of NTM in our water system yet. Thus, the general objective of this study is to establish the presence of NTM in raw, post-treated and tap water being supplied by a water concessionaire in Metro Manila. A total of 45 water samples were obtained from raw-post-treated, and tap water sources. Each sample has undergone decontamination and neutralization (for raw water samples), membrane filtration, and cultivation on Middlebrook 7H10 with OADC Enrichment for eight weeks. Colonies were then evaluated by morphology and acid-fastness. Only acid-fast bacilli colonies which are positive to catalase test at 68 degrees Celsius were submitted for 16S rRNA identification to Accugenix, USA. Three species of NTM were isolated in tap water samples from three different cities (Quezon City, Malabon City and Caloocan City) in Metro Manila: Mycobacterium gordonae, Mycobacterium mucogenicum/phocaicum, and Mycobacterium sp. from a health center, elementary school and household, respectively. However, there were no NTM isolated from raw and post-treated water samples. This study is the first to detect NTM in our water system. The existence of the NTM isolated in tap water may pose a health risk to immunocompromised and healthy individuals in the country. With the results of the present study showing the occurrence of these important pathogens, this will help in the assessment of local tap water and possible risks to susceptible hosts in the Philippines.